Diverse residents’ experiences of policing and attitudes towards law enforcement: Findings from a large community-based survey in San José, California - Soma de Bourbon; Michael Dao; Melissa McClure Fuller; William Armaline; Curtis Asplund; Rachel Kumar; Daniel DeSanto; Jaala Robinson; Derrick Sanderlin; Miranda Worthen (PLoS ONE, 2025)
Despite widespread debate on public safety policy, few studies explore diverse community members’ perspectives on safety and policing. This community-based participatory research study assessed perspectives on city spending, opinions about law enforcement policy, perspectives on police and safety, direct experiences with police, and perspectives on alternatives to policing in San José, California, one of the ten largest cities in the United States. Between July 27, 2021 – January 14, 2022, we conducted an online survey, available in 7 languages, and obtained 1,595 responses. Respondents supported increased funding for community safety resources (73%) and helping residents meet basic needs (67%). A majority of respondents felt policing in San José had serious problems, requiring major reform. Across a range of questions, sexual and gender minorities, younger people, African American/Black, Native American, Chicanx/Latinx/Hispanic respondents, and people with lower incomes had more negative attitudes towards and experiences with police compared to those who identify as men, heterosexual, older, White or Asian, or had higher incomes. There was strong support (72% − 82%) for four alternative-to-police policy proposals. As communities across the country grapple with how to achieve safety, especially for residents who are disproportionately harmed by police, community-based participatory research is a valuable tool for engaging, understanding, and mobilizing communities.